2004
DOI: 10.1196/annals.1297.047
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Telomere Shortening by Oxidative Stress

Abstract: We investigated whether oxidative stress, which contributes to aging, accelerates the telomere shortening in human cultured cells. The terminal restriction fragment (TRF) from WI-38 fibroblasts irradiated with UVA (365-nm light) decreased with increasing of the irradiation dose. Furthermore, UVA irradiation dose-dependently increased the formation of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) in both WI-38 fibroblasts and HL-60 cells. In order to clarify the mechanism of the acceleration of telomere shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
298
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(325 citation statements)
references
References 10 publications
(11 reference statements)
9
298
2
6
Order By: Relevance
“…These results indicate that the photoexcited endogenous photosensitizer specifically oxidizes the central guanine of 5'-GGG-3' in telomere sequence to produce 8-oxodG probably through an electron transfer reaction. It is concluded that the site-specific damage in telomere sequence induced by UVA irradiation participates in the increase of the telomere shortening rate (41,42).…”
Section: The Role Of Reactive Oxygen Species In Agingmentioning
confidence: 99%
“…These results indicate that the photoexcited endogenous photosensitizer specifically oxidizes the central guanine of 5'-GGG-3' in telomere sequence to produce 8-oxodG probably through an electron transfer reaction. It is concluded that the site-specific damage in telomere sequence induced by UVA irradiation participates in the increase of the telomere shortening rate (41,42).…”
Section: The Role Of Reactive Oxygen Species In Agingmentioning
confidence: 99%
“…It has been reported that oxygen-derived free radicals directly damage the guanine repeats in the telomere DNA (24)(25)(26)(27). This means that oxidative stress leads to telomere erosion, with no requirement for cell division, resulting in cellular senescence.…”
mentioning
confidence: 99%
“…In addition, fibroblasts of FA patients demonstrated shorter telomeres and higher rates of telomere attrition compared to their normal age-matched counterparts (Adelfalk et al, 2001;. The accumulation of breaks at telomeres after exposure to oxidative stress and the subsequent increase in of 8-oxodG content at telomeres of human fibroblasts were reported in vitro (Von Zglinicki et al, 2000a;Kawanishi & Oikawa, 2004) and in vivo in differentiating cells, in addition to native replicative shortening during lymphocyte proliferation (Callen et al, 2002).…”
Section: Discussionmentioning
confidence: 97%